The Process of Critical Thinking Ability in the PBL Model Viewed from Independent Learning - Ali Wardana; YL Sukestiyarno; Wardono Wardono (International Conference on Science, Education, and Technology, 2022)
Critical thinking ability is a tool that can be used to face challenges and survive. In addition to critical thinking skills, there are also affective aspects that need to be developed in learning activities, namely self-learning aspects. Independent learning will have a significant impact on student learning outcomes. This study aims to describe the process of mathematical critical thinking and identify the level of students' mathematical critical thinking given to learning mathematics. This study used qualitative research methods. The research subjects were 10 students who were taken from 33 high school class X students who were selected based on their initial mathematical ability. Research instruments include researchers, critical thinking tests, and interview guidelines. The data collection technique used consisted of critical thinking tests and teacher and student interviews. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. The results showed that students who are independent in learning have the ability to think critically because these students can fulfill all stages of critical thinking when solving a given problem.